2023
DOI: 10.1039/d3fo01060k
|View full text |Cite
|
Sign up to set email alerts
|

Bromelain: a review of its mechanisms, pharmacological effects and potential applications

Abstract: The utilization of plant-derived supplements for disease prevention and treatment has long been recognized for their remarkable potential. Ananas comosus, commonly known as pineapple, produces a group of enzymes called...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 156 publications
(235 reference statements)
1
0
0
Order By: Relevance
“…The most commonly reported side effects in the literature were stomach upset and diarrhea, increased heart rate, hives and throat tightness even if for very high doses and, in any case, not frequently [21]. In the present study, no side effects were reported in short-term and distant controls.…”
Section: Discussionsupporting
confidence: 51%
“…The most commonly reported side effects in the literature were stomach upset and diarrhea, increased heart rate, hives and throat tightness even if for very high doses and, in any case, not frequently [21]. In the present study, no side effects were reported in short-term and distant controls.…”
Section: Discussionsupporting
confidence: 51%
“…Since its discovery, numerous in vitro and in vivo studies have shown that bromelain has various phytomedical activities: anti-inflammatory, fibrinolytic, anti-coagulative, antithrombotic, drug absorption-enhancing, and, most interestingly, anticancer actions [ 81 , 83 , 85 , 89 ]. Even though the anticancer effect is mainly due to enzymatic activity, some studies have highlighted that the non-enzymatic components of bromelain (polysaccharides, glycoproteins, vitamin C, β-carotene, and flavonoids) have a synergistic impact on the complex network involved [ 82 , 90 ]. Numerous studies have shown that, depending on the milieu, bromelain modulates the immune response in different ways.…”
Section: Bromelainmentioning
confidence: 99%